THE ECLECTIC STYLE OF CHURCHES WITH TRADITIONAL ARCHITECTURE IN BALI - WAHYU SUKAYASA (NIM 27103006); Pembimbing: Dr. Biranul Anas Z., dan Dr.I Bambang Soegiharto, KOMANG
The study was conducted due to the writerÃ‚Â’s interest towards the eclectic phenomena which causes changes in the architecture and interior of churches with Balinese traditional architecture for the Protestants and the Catholics in Bali. The phenomena of the architectural development of churches above shows that part of it is the development of local traditional culture and another part of it is the development of outside/original or modern culture, a number of churches which develop local culture through adaptation of traditional architecture. The phenomena is a development of (absorption, taking of and use of) elements of (form and space design) traditional architecture into church architecture, indirectly has created the traditional of church architecture which is specific and different with the ones developed in its original place. This is reveled through synthesis result of adaptation on the visual expression and true principle, which reflects the tie of close communication between church architecture with Christian community in Bali. Several components, especially the component of true principle, is not entirely adapted, that is related to ideas, values, viewpoints, theories and beliefs of individuals. The specific elements of churches have mainly been replaced with specific elements of traditional architecture. The condition of Christian community which is a minority creates the church itself into symbol of attitude of Christians towards the surrounding environment. To analyse changes taking place, a provision from the decision of Sidang Sinode Abianbase for Protestant Church and Kansili Vatikan II was used, which is the background of the use of Balinese traditional architecture on Churches. The architectural elements analysed covered plan, shape of building, parts of building, the use of ornaments and symbols. The result of analysis on the changes in architecture and interior will be compared with form and meaning of building in Balinese traditional architecture. From the analysis, the writer concluded that the eclectic pattern implemented on churches with traditional architecture in Bali with differences in pattern between Catholic and Protestant churches is caused by the difference in concept of spread of Christianity and the understanding on redefinition process of elements of Balinese traditional architecture on churches.